Simulation and Design of Modified Adaptive-based Maximum Power Point Tracking Methods for Photovoltaic Systems - J, Surya Kumari; P, Sarala; D, Lenine; Ch, Sai Babu; J, Kanna Kumar (International Journal of Integrated Engineering, 2024)
The quality of the supplied electrical energy is becoming increasingly stringent as the use of energy grows. As traditional energy sources grow depleted and the cost of electricity rises, photovoltaic energy emerges as a possible option. A growing number of people are turning to photovoltaic (PV) generation as a renewable energy source due to its many benefits, including low maintenance and quiet operation. This research compares the most widely used MPPT algorithms which are the Adaptive fixed duty ratio method (AFDR) and the Adaptive variable duty ratio method (AVDR). In this paper the simulation and analytical analysis for the two MPPT techniques of AFDR and AVDR for the PV System under three methodologies such as irradiation, duty cycle variations of the converter, and load variations. From the results, it was found that AVDR increased the PV output power and the AVDR method has proved that it has fast transient convergence with a better steady-state tracking efficiency.